The Newly Described Heterotrophic Dinoflagellate Gyrodinium moestrupii, an Effective Protistan Grazer of Toxic Dinoflagellates. (28th November 2012) - Yoo, Yeong Du; Yoon, Eun Young; Jeong, Hae Jin; Lee, Kyung Ha; Hwang, Yeong Jong; Seong, Kyeong Ah; Kim, Jae Seong; Park, Jae Yeon
Abstract Few protistan grazers feed on toxic dinoflagellates, and low grazing pressure on toxic dinoflagellates allows these dinoflagellates to form red‐tide patches. We explored the feeding ecology of the newly described heterotrophic dinoflagellate Gyrodinium moestrupii when it fed on toxic strains of Alexandrium minutum, Alexandrium tamarense, and Karenia brevis and on nontoxic strains of A. tamarense, Prorocentrum minimum, and Scrippsiella trochoidea. Specific growth rates of G. moestrupii feeding on each of these dinoflagellates either increased continuously or became saturated with increasing mean prey concentration. The maximum specific growth rate of G. moestrupii feeding on toxic A. minutum (1.60/d) was higher than that when feeding on nontoxic S. trochoidea (1.50/d) or P. minimum (1.07/d). In addition, the maximum growth rate of G. moestrupii feeding on the toxic strain of A. tamarense (0.68/d) was similar to that when feeding on the nontoxic strain of A. tamarense (0.71/d). Furthermore, the maximum ingestion rate of G. moestrupii on A. minutum (2.6 ng C/grazer/d) was comparable to that of S. trochoidea (3.0 ng C/grazer/d). Additionally, the maximum ingestion rate of G. moestrupii on the toxic strain of A. tamarense (2.1 ng C/grazer/d) was higher than that when feeding on the nontoxic strain of A. tamarense (1.3 ng C/grazer/d). Thus, feeding by G. moestrupii is not suppressed by toxic dinoflagellate prey, suggesting that it is an effective protistan grazer of toxic dinoflagellates.